The ozone concentration and tree vitality at the metropolitan zone of Guadalajara - Macías-Muro, Alejandra; Martínez-Trinidad, Tomás; Valdez-Lazalde, José René; Vaquera-Huerta, Humberto (Ecosistemas y Recursos Agropecuarios, 2023)
Air pollution, par ticularly tropospheric ozone (O3 ), when present in high concentrations, affects urban tree health. This study analyzed the ozone concentration and the potential effect on the vitality of the trees located in the metropolitan area of Guadalajara. Data from the Jalisco air quality monitoring network and photosynthetic activity through chlorophyll fluorescence of Fraxinus uhdei, Eucalyptus camaldulensis, and Casuarina equisetifolia were studied. A generalized extreme value model was fitted to estimate the atmospheric distribution and identify areas with the highest concentration of ozone. An analysis of variance was carried out to evaluate possible changes in the condition of the vitality due to the ozone concen- tration in the atmosphere. The areas with the highest ozone concentration were in Tlaquepaque, Zapopan, and the northeast of Guadalajara. No significant effect of areas with higher ozone concentrations on tree vitality was observed.